A Case study on the current state of in-service training in a public school based on teachers' and administrators' evaluation - Ala, Hüseyin. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2010., 2010)
This case study examines the current state of in-service training activities in a public school based on teachers’ and administrators’ evaluation. It is a qualitative analysis addressing three categories of questions which relate to the current state of in-service training activities in a public school along with teachers’ and administrators’ evaluation of in-service training activities provided by the Ministry of National Education. The participants of the study are the teachers and administrators of a public elementary school situated in a low income, high migration area in Ümraniye, Istanbul. Regarding the data collection, in the first phase, there was an analysis of documentation and an interview with the assistant manager responsible for the implementation of in-service trainings was performed to understand the current situation of in-service training activities in the school. In the second phase of the study, semi-structured interviews were applied according to the Teachers’/Administrators’ Evaluation of In-Service Training: Semi Structured Interview Form. The findings indicated that the school where this research was performed had brought about a general perspective on the current instances of in-service training and opened new matters of discussion related to the design of in-service training practices. There appear significant problems regarding teachers’ and administrators’ approaches toward in-service training, trainers, time, place, prior analysis of needs and trainings on technology.
Keywords: Elementary school teachers -- In-service training -- Turkey.; Teachers -- In-service training -- Turkey.